Best Answer

8b + 11 - 3b = 2b + 2

5b + 11 = 2b + 2

5b - 2b = 2 - 11

3b = -9

b = -3

Q: If 8b plus 11-3b equals 2b plus 2 what is b?

Write your answer...

Submit

Still have questions?

Continue Learning about Algebra

5b2 = 8b therefore 5b =8 therefore b = 1.6

They are 3 terms of an algebraic expression

8b - 4b = 4b

Well if it is worded right then 4xb-1+(-4)+4b=4b-1-4+4b=4b+4b-1-4=8b-5

b(6a-8) if you are factoring

Related questions

That's an equation in which b = -1

10a - 10 b

4(2b+5)

4(a + 2b - 4c)

Amazing! Exactly the same question was posted here on WikiAnswerslast September 23. What an incredible coincidence!8b + 11 - 3b = 2b + 2That 8b on the left side can be combined with the -3b to make 5b .5b + 11 = 2b + 2Subtract 2b from each side:3b + 11 = 2Subtract 11 from each side:3b = -9Divide each side by 3:b = -3(That's the same answer they got last September.)

8b = e - 12n, possibly.

8b = -65 so b = -8.125

Two equations, two unknownsFirst, multiply 3a + 2b = 70 by 4. This gives the equation 12a + 8b = 96. Next, subtract 4a + 8b = 70 from this equation. This result gives 8a = 26, which, solving for a, gives a = 3.25.Substitue the value of a into one of the original equations, which will give b = 7.125.Finally check your results by substituting the values of a and b into each equation.Answer:Given two equations 3a + 2b = 24 ------ (1) and 4a + 8b = 70 ------ (2) We have to solve this by using elimination method.Multiply the equation 3a + 2b = 24 by 4 on both the sides.We get 12a + 8b = 96 ---------- (3)Now, subtract the equation (2) from equation (3)12a + 8b = 96 ---------- (3)4a + 8b = 70 ---------- (2)--------------------------------(12a - 4a) + (8b - 8b) = (96 - 70)8a + 0 = 268a = 26a = 26/8a = 13/4 (Or) a = 3.25Substitute the value of a in the equation (2)4a + 8b = 70 ---------- (2)4(13/4) + 8b = 70.13 + 8b = 708b = 70 - 138b = 57b = 57/8 (Or) b = 7.125

6a + (7b - 4a - 8b) = (6a - 4a) + (7b - 8b) = 2a - b

-2

7b + 16 = 5b + 247b - 5b = 24 - 162b = 8b = 4

If you mean 2a8b - 5 = x and a2b = 5, then: 2(54) - 5 = x x = 1350 - 5 x = 1345